Grain-size distribution analysis of Quaternary sediments from the southern part of the Lodz region in Poland: a computational-methods approach - Wachecka-Kotkowska, Lucyna; Kotkowski, Paweł (Geologos, 2012)
Eighteen samples of Quaternary unconsolidated sediments from the Piotrków Plateau and the Radomsko Hills in central Poland have been analysed for their average grain size, sorting, skewness and kurtosis. The analysis was carried out by seven computational methods of interpolation and nine extrapolation methods. It appears that linear interpolation, the traditional method (DOS), and the Josek and Gradistat Programs give comparable results, but that quadratic interpolation and the method of moments should not be applied since they yield unreliable results. The method of moments gives unduly high or unduly low parameter values because of the application of different, i.e. incomparable measures in the applied formulae. It should be stressed that only extrapolation provides, if performed under the right conditions, the possibility to determine some parameters, in particular skewness values.